Optimisation of CH4 and CO2 conversion and selectivity of H2 and CO for the dry reforming of methane by a microwave plasma technique using a Box–Behnken design - Alawi, N.; Barifcani, Ahmed; Abid, H. (John Wiley & Sons, Ltd, 2018)
A microwave plasma was generated by N2 gas. Synthesis gases (H2 and CO) were produced by the interaction of CH4 and CO2 under plasma conditions at atmospheric pressure. The experimental pilot plant was set up, and the gases were sampled and analysed by gas chromatography–mass spectrometry. The Box–Behnken design (BBD) method was used to find the optimising conditions based on the experimental results. The response surface methodology based on a three-parameter and three-level BBD has been developed to find the effects of independent process parameters, which were represented by the gas flow rates of CH4, CO2, and N2 and their effects on the process performance in terms of CH4, CO2, and N2 conversion and selectivity of H2 and CO. In this work, four models based on quadratic polynomial regression have been determined to understand the connection between the limits of the feed gas flow rate and the performance of the process. The results show that the most important factor influencing the CO2, CH4, and N2 conversion and the selectivity of H2 and CO was “CO2 feed gas flow rate.” At the maximum desirable value of 0.92, the optimum CH4, CO2, and N2 conversion were 84.91%, 44.40%, and 3.37%, respectively, and the selectivities of H2 and CO were 51.31% and 61.17%, respectively. This was achieved at a gas feed flow rate of 0.19, 0.38, and 1.49 L min-1 for CH4, CO2, and N2, respectively.